PERAN PEMERINTAH DALAM RESOLUSI KONFLIK HUBUNGAN INDUSTRIAL DI PT. DUTA PALMA NUSANTARA KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI 2011– 2014 - Fuqaha, M. Fatah; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In this study can be found some of the impact of the conflict between labor and management PT.Duta Palma Nusantara Benai District of Kuantan District Singingi than in 2011-2014, namely, theGovernment tried to mediate the two sides but PT. Duta Palma never ignore what the Government, LocalGovernment several times to try to mediate again, but failed because the PT. Duta Palma did not come in theinvitation, PT. Duta Palma has negotiate it conflicts with other labor representatives, but the results are alsoworkers' demands were not met.This study uses a qualitative method with descriptive data assessment. In collecting the data theresearcher used interview, observation and documentation. By using key informants as sources of information.The results showed that on the Role of Government in Industrial Relations Conflict Resolution at PT.Duta Palma Nusantara is bipartite settlement which biparit settlement or by consensus have been conductedand the agreement has been designed to be but one of the negotiating parties do not meet the demands thathave been agreed upon. Mediation has been done by the parties concerned with the involvement ofgovernment as penengahnya all the problems have been submitted and obtained a decision to meet thedemands of both parties desired. The Government has given a pleasant decision for both parties but as aresult of the settlement made by the company does not provide information to workers that demands that theworkers agreed. The workers do a submission to court for the settlement of the conflict with the results of thecompany will fulfill our demands, with the settlement we submitted to court we will get a win and demandsthat we wanted.Keywords : Conflict Resolution, Industrial Relations, The Role of Government